SWEAR WORDS AMONG UNIVERSITY STUDENTS IN BANDUNG: A MIXED-METHODS SOCIOLINGUISTIC STUDY OF TYPES, PURPOSES, AND INFLUENCES - Puspita Sari; Hero Gunawan (University of Kuningan, 2026)
This study investigates the use of swear words among university students in Bandung, focusing on the types, purposes, influences, and gender differences in swearing behavior. Through a mixed-method approach comprising surveys, interviews, and observational data, the study reveals that students use a diverse range of swear words, including local vernacular and borrowed terms from English, primarily to express emotions, build social bonds, emphasize communication, and challenge societal norms. According to the findings, peer pressure, media exposure, cultural background, and digital platforms all have a substantial influence on swearing practices. There are notable gender inequalities, with male students swearing more frequently and openly than their female colleagues, who tend to use softer phrases in private. The role of social media platforms in normalizing swearing and fostering linguistic creativity is particularly highlighted. These findings underscore the complex interplay between cultural, social, and technological factors in shaping language use among youth. This study contributes to the broader understanding of sociolinguistic behavior in modern, digitalized societies.